Peran UMKM Dalam Mengurangi Tingkat Pengangguran Masyarakat dan Strategi UMKM Ditengah Pandemi Covid-19 - Nida Alfi Nur Ilmi (Jurnal Manajemen dan Bisnis, 2021)
ABSTRACT This paper tries to explain and describe the position of UMKM in the Kepuh, Boyolangu Village, Banyuwangi, as an effort to reduce the unemployment rate, especially in the lower middle class and to see how the strategy of the UMKM founders in maintaining their position in all conditions. So it is hoped that readers can find out and analyze UMKM within the scope of the region as an effort to minimize unemployment and increase living standards. This paper use qualitative research method with a qualitative descriptive approach. Establishing UMKM is certainly not an easy thing, because the large number of workers does not guarantee UMKM, who is determined by the appropriate expertise and strategy. In addition, the Government has not been maximally perfect in overcoming problems and financial assistance for community UMKM which in reality is able to absorb many new workers, and has an impact on reducing the unemployment rate.